Research on the Controlling Effect of NPR Cables for Anti-Dip Slope Based on the Numerical Simulation - Xiaohu Zhang (Hindawi Limited, 2021)
As the scale and depth of mines increase, large deformations of high-steep slopes progressively become prominent. Compared with the ordinary cables, negative Poisson’s ratio (NPR) cables can provide a constant resistance force and high deformation inhibition during slope deformation, avoiding the occurrence of slope instability hazards. Consequently, the control effects on the toppling failures of slopes were necessary to be researched. Changshanhao open-pit gold mine was taken as an example; based on the field geological investigation and rock mechanics testing, a three-dimensional engineering geological model of open-pit mine was constructed. Subsequently, the stability of open pit in current situation and final boundary situation was estimated with FLAC3D software, for the potential slope vulnerable areas to be comprehensively identified. Finally, the control effects of ordinary cables and NPR cables on the instable W13 slope section were compared and studied through FLAC3D simulations, and the reinforcement effects of NPR cable on the anti-dip slope were proved as significant; meanwhile, the corresponding reinforcement methods in the failure mine areas were proposed, laying a reference for the instability failure control and reinforcement of similar anti-dip slopes.